Implementasi Pendidikan Karakter dalam Pembelajaran - Julaiha, Siti (Dinamika Ilmu, 2014)
The education institutions become a central place to create a young better generation than the privous ones through character education. The character education is a process of creating the students become an intactly good-characterized human in the dimension of mind, way of thinking, physically healthy, and hearted human. The character education is carving the studentsâ ahlaq through a process of knowing the good, loving the good, and acting the good. That process involves the coqnitive, emotional, and physical aspects, so the noble ahlaq can be carved become the habit of the mind, heart, and hands. The character education is directed to create a tough, competitive, noble hearted, moraly, tolerant, helpful, patriotic, and dinamic person who has the orientation of science and knowledge based on the belief and piety of Allah SWT. A teacher implements the character education in the teaching and learning process by making the students formulate the questions actively, find the sources of learning, collect the information, work with the information, reconstruct the fact, and present the result of reconstruction. The character education learning should be done by the teachers from the planning, implementaion, and evaluation.